The Relationship Between Distributive Leadership and Organizational Change Management Strategies - Wan Muda, Wan Hanim Nadrah; Fazlinda Ab Halim; Lai Chee Sern; Khairunesa Isa; Atif Saleem; Norzeha Othman (Journal of Technical Education and Training, 2024)
This study explores the relationship between distributive leadership and change management strategies in Malaysian vocational colleges. Distributive leadership is vital for implementing Malaysia’s Education Development Plan 2013-2025, particularly in enhancing leadership effectiveness. Effective organizational transformation depends on leaders’ styles and abilities to manage changes efficiently and continuously. This research examines the extent of distributive leadership practices among vocational college leaders in Malaysia and explores variations based on demographic characteristics. Conducted with a sample of 254 vocational college teachers across nine states, data were collected through a questionnaire distributed via Google Forms. The questionnaire comprised two sections: Perceptions of Distributive Leadership Practices and Change Management Strategies. Data were analyzed using descriptive and inferential statistics with SPSS Version 26.0. Findings indicate that respondents generally agree with the principles of distributive leadership, including bounded empowerment, leadership development, shared decision-making, and collective engagement. Additionally, a positive relationship was found between distributive leadership and change management strategies. To optimize change management, leaders should engage managers, employees, and senior leaders.